2015
DOI: 10.28945/2160
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Facebook and Twitter has on the Cognitive Social Capital of University Students

Abstract: The impact that Social Media, such as Facebook and Twitter, usage has on the creation and maintenance of university students' cognitive social capital was investigated on students in the Western Cape Province of South Africa. Facebook and Twitter were selected as part of the research context because both are popular online social network systems (SNSs), and few studies were found that investigated the impact that social media has on the cognitive social capital of South African university students. Data was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Ellison et al (2007) briefly put forward that the core factor of this concept is interpersonal relationship and reciprocal value. As one of the most commonly used concepts in various academic fields, social capital has successfully extended its scope to online space to emphasize the positive consequences of various online communication tools (Hofer & Aubert, 2013; Petersen & Johnston, 2015). In fact, social media, as an alternative platform, is particularly suitable for cultivating social capital at the individual level, because it strengthens the linkages between different social relationships (Pang, 2018).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Ellison et al (2007) briefly put forward that the core factor of this concept is interpersonal relationship and reciprocal value. As one of the most commonly used concepts in various academic fields, social capital has successfully extended its scope to online space to emphasize the positive consequences of various online communication tools (Hofer & Aubert, 2013; Petersen & Johnston, 2015). In fact, social media, as an alternative platform, is particularly suitable for cultivating social capital at the individual level, because it strengthens the linkages between different social relationships (Pang, 2018).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In this study, consultation outside the classroom is known as Out-of-Class Communication (OCC). OCC have been observed to be varied but not limited to short message service (Abu and Abdul, 2012) and social networks (Petersen and Johnston, 2015;Woods et al, 2012). Kansanen (1999) describes this phase as a convenient and effective means of interaction.…”
Section: Take Down Policymentioning
confidence: 99%
“…Other empirical studies, however, have revealed that an individual’s interactions with social media are related to increased feelings of depression, loneliness, and stress (e.g., [ 44 , 48 , 63 ]). A few studies have even suggested that social media use is not related, positively or negatively, to one’s psychosocial outcomes (e.g., [ 58 , 78 ]).…”
Section: Introductionmentioning
confidence: 99%